Influencia de la defoliación parcial en plantas de soja (Glycine max.) - Rosas, G. S. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A study was carried out at the Pergamino Experiment Station, Argentina, in order to evaluate the effect of certain biting and cutting larvae of Plusia nu, Colias lesbia, Heliotis armigera and others, on the quantity of capsules, seed production and percentage of oil and protein of the seeds in soya plants (Glycine max). The defoliation produced by those larvae was simulated by cutting the leaves in percentages of 8.3 to 50% of their area and at different ages of the plant, from 15 to 75 days of age. It was found a negative influence of the defoliation on the quantity of capsules and seed production. No influence was found on the oil and protein content of the seeds